2011
DOI: 10.1111/j.1750-3841.2011.02063.x
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characterization and Antioxidant Activities of 2 Water‐Soluble Polysaccharide Fractions Purified from Tea (Camellia sinensis) Flower

Abstract: At present, commonly low-grade tea is preferred to extract the tea polysaccharide, to take full advantage of tea flower resource to extract polysaccharides can greatly reduce the cost of tea products. Thus, the search for plant-derived biomaterials from this study could generate natural value-added products from underutilized tea plant waste and used as a medicinal agent against chronic health problems, such as cancers, aging, and atherosclerosis caused by reactive free radicals that produced from oxidation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(31 citation statements)
references
References 60 publications
(55 reference statements)
0
31
0
Order By: Relevance
“…AFM is a powerful technique for directly observing the conformation of macromolecules under conditions that closely mimic the environments from which they originated (Han et al, 2011; Wang J. et al, 2014). It is clear from these images that the exopolysaccharide is linear and crossover in structure and branched or coiled in aqueous solution.…”
Section: Resultsmentioning
confidence: 99%
“…AFM is a powerful technique for directly observing the conformation of macromolecules under conditions that closely mimic the environments from which they originated (Han et al, 2011; Wang J. et al, 2014). It is clear from these images that the exopolysaccharide is linear and crossover in structure and branched or coiled in aqueous solution.…”
Section: Resultsmentioning
confidence: 99%
“…The antioxidant activities of polysaccharides are mainly associated with their characteristics, such as their monosaccharide compositions and molecular weights 43 . The monosaccharide compositions and molecular weights of EPS and DEPS were investigated in this study.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that cell wall of tea leaves and flowers contain water soluble polysaccharides which has immense health benefits like antioxidant, hypoglycemic, anti HIV, anti cancer, anti blood coagulant, anti radiation, and hepatoprotective (Quana et al 2011;Nie and Xie 2011;Xu et al 2012).…”
Section: Extraction Of Polysaccharide From Tea Leaves and Flowersmentioning
confidence: 99%